2021
DOI: 10.3390/ijerph18062857
|View full text |Cite
|
Sign up to set email alerts
|

Association of Nursing Work Environment, Relationship with the Head Nurse, and Resilience with Post-Traumatic Growth in Emergency Department Nurses

Abstract: Emergency department nurses are confronted with unpredictable diseases and disasters and work-related traumatic stress events. This study aimed to examine the relationship between nursing work environment, relationship with the head nurse, resilience, and posttraumatic growth among emergency department nurses. Data were collected from December 2018 to February 2019 through a self-administered survey questionnaire. Participants comprised 127 nurses working in the emergency department. The collected data were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 36 publications
(60 reference statements)
1
27
0
Order By: Relevance
“…However, in the present study, no significant difference was found between the participants' psychological resilience levels in terms of variables such as sex, marital status and being or not being diagnosed with Covid‐19. In this regard, our results are consistent with Han et al's ( 2020 ) and Jung and Park's ( 2021 ) results.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, in the present study, no significant difference was found between the participants' psychological resilience levels in terms of variables such as sex, marital status and being or not being diagnosed with Covid‐19. In this regard, our results are consistent with Han et al's ( 2020 ) and Jung and Park's ( 2021 ) results.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, it can be said that such spiritual feelings significantly increase nurses' psychological resilience. Similarly, in a study conducted in Korea by Jung and Park ( 2021 ), nurses who stated that they liked their job had a higher level of psychological resilience. However, in the present study, no significant difference was found between the participants' psychological resilience levels in terms of variables such as sex, marital status and being or not being diagnosed with Covid‐19.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The percentage values of high ratings were: 65.4%, 32.1%, and 12.4% in the groups of nurses declaring that working conditions are excellent, good and unsatisfactory, respectively. Research by other authors confirms that a positive work environment of nurses, including working conditions and specific features of the ward significantly influence work satisfaction, engagement and care quality [10,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the presented research may have an impact on the improvement of patient safety, provided that the management is open to the prospects linking patient safety with the working conditions of nurses. Numerous studies show that organisational features of nurses' work environment have a significant influence on patients' safety [6,[10][11][12]. Aiken et al highlighted the necessity of creating an optimal work environment for nurses [13].…”
Section: Of 14mentioning
confidence: 99%